Genetic Characterization of a French Cohort of GNE‐mutation negative inclusion body myopathy patients with exome sequencing. Issue 5 (7th April 2017) - Cerino, Mathieu; Gorokhova, Svetlana; Laforet, Pascal; Ben Yaou, Rabah; Salort‐Campana, Emmanuelle; Pouget, Jean; Attarian, Shahram; Eymard, Bruno; Deleuze, Jean‐François; Boland, Anne; Behin, Anthony; Stojkovic, Tanya; et al.
ABSTRACT: Introduction: Hereditary inclusion body myopathy (hIBM) refers to a group of clinically and genetically heterogeneous diseases. The overlapping histochemical features of hIBM with other genetic disorders lead to low diagnostic rates with targeted single‐gene sequencing. This is true for the most prevalent form of hIBM, GNEpathy. Therefore, we used whole‐exome sequencing (WES) to determine whether a cohort of clinically suspected GNEpathy patients undiagnosed by targeted GNE analysis could be genetically characterized. Methods: Twenty patients with hIBM but undiagnosed by targeted GNE sequencing were analyzed by WES before data filtering on 306 genes associated with neuromuscular disorders. Results: Seven patients out of 20 were found to have disease‐causing mutations in genes associated with hIBM or genes allowing for hIBM in the differential diagnosis or associated with unexpected diagnosis. Discussion: Next‐generation sequencing is an efficient strategy in the context of hIBM, resulting in a molecular diagnosis for 35% of the patients initially undiagnosed by targeted GNE analysis. Muscle Nerve 56 : 993–997, 2017